Political Norm and Sickness in Patria o muerte, by Alberto Barrera Tyszka - Baltodano Román, Gabriel (2019)
An analysis is presented of Patria o muerte (2015), by Alberto Barrera Tyszka, a novel about the sickness and death of Hugo Chávez. It establishes symbolic relations between the body and health of the ruler and the political order and contemporary history of Venezuela. Within the framework of the literary tradition about caudillismo, the novelty of the work is related to the use of argumentative strategies for normative purposes within traditional ideology, based on hygienist logic. It focuses on the metaphors of the disease and the naturalization of certain political visions.